A Ruthenium(II) complex based long lifetime phosphorescent probe for copper ions and pH detection - Yan Chen; Xufeng Mai; Jiecheng Zhao; Cuiqin Huang; Jun Li; Zhuopeng Ruan; Huijuan Yu (KeAi Communications Co., Ltd., 2023)
Objective: Transition metal ruthenium(II) complex was used to prepare a dual-functional phosphorescent probe for the detection of Cu2+ ion and pH. Methods: The ligand (E)-6-((thiazol-2-yl methylene)amino)-1,10-phenanthrolin-5-amine (tmpa) was prepared by condensation of 5,6-diamine-1, 10-phenanthroline with 2-formylthiazole, and then ruthenium(II) complex [Ru(bpy)2tmpa](PF6) (Ru-tmpa, bpy ​= ​2,2'-bipyridine) was synthesized by the coordination of tmpa with cis-Ru(bpy)2Cl2. Phosphorescence spectra were measured to investigate its response to metal ions (Li+, Na+, K+, Mg2+, Ca2+, Mn2+, Pb2+, Cr2+, Co2+, Ni2+, Cu+, Cu2+, Fe3+, Fe2+ and Zn2+). The binding affinity and detecting limit of Ru-tmpa to copper ions were tested by titration experiment. The ability of the probe to monitor copper ion levels inside cells was tested by confocal microscopy imaging. Results: Ru-tmpa can rapidly, sensitively and selectively detect Cu2+ in water and biological sample, and shows a sensitive phosphorescence response to pH. Ru-tmpa can penetrate cell membrane, enter the cell, and monitor the level of copper ions inside cell. Conclusion: A novel fluorescent probe Ru-tmpa was synthesized to provide a powerful tool for the detection of Cu2+ and pH in biological and environmental systems.